Dietary copper affects antioxidant and immune activity in hybrid tilapia (Oreochromis niloticus × Oreochromis aureus). (30th January 2017) - Tang, L.; Huang, K.; Xie, J.; Yu, D.; Sun, L.; Huang, Q.; Bi, Y.
Abstract: Copper (Cu) is an essential nutrition trace element for Tilapia. However, the molecular mechanisms for the effects of Cu on Tilapia remain unknown. To explore the mechanism, 2, 160 hybrid tilapia ( Oreochromis niloticus × Oreochromis aureus ) fries were used and evenly assigned to six groups and fed with different concentrations of Cu. After 60‐day culture, physiological characters and biochemical parameters were measured. Spleen somatic index (SSI) was analysed, and distribution of trace elements was investigated. qRT‐PCR was used to analyse the levels of immune genes. The result showed that 17 mg kg −1 of dietary Cu improved the growth rate, survival rate (SR), weight gain rate, condition factor and feed conversion ratio of hybrid tilapia ( p  <   .05). Meanwhile, the dietary Cu increased the activity of superoxide dismutase and reduced the activity of glutathione (GSH), alanine aminotransferase, aspartate aminotransferase and lysozyme ( p  <   .05). Sixteen mg kg −1 of dietary Cu did not affect SSI. Furthermore, dietary Cu affects the levels of immune genes, interleukin‐1, tumour necrosis factor, MHC class IIB, pre‐B‐cell leukaemia transcription factor 1 and P450. Therefore, a certain concentration of Cu can improve tilapia performance by affecting its antioxidant and immune activity.